LMPA Regulates Lesion Mimic Leaf and Panicle Development Through ROS-Induced PCD in Rice - Hu, Peng; Tan, Yiqing; Wen, Yi; Fang, Yunxia; Wang, Yueying; Wu, Hao; Wang, Junge; Wu, Kaixiong; Chai, Bingze; Zhu, Li; Zhang, Guangheng; Gao, Zhenyu; et al. (Frontiers in Plant Science, 2022)
Leaf and panicle are important nutrients and yield organs in rice, respectively. Although several genes control lesion mimic leaf and panicle abortion have been identified, there are few reports involved in both traits regulated by one gene. In this study, we characterized a panicle abortion mutant, lesion mimic leaf and panicle apical abortion (lmpa), which exhibits lesions on leaves and degeneration of apical spikelets. Molecular cloning revealed that LMPA encodes a proton pump ATPase protein localized on the plasma membrane, which is highly expressed in leaves and panicles. Promoter activities analysis showed that the fragment inserted in the promoter of lmpa caused a decrease in transcription level. Cellular and histochemistry analysis indicated that the ROS accumulated and cell death occurred in lmpa. Moreover, physiological experiments revealed that the lmpa was more sensitive to temperature and salt stress. These results provide a better understanding of the role of LMPA in panicle development and lesion mimic formation by regulating ROS homeostasis.